1997
DOI: 10.1073/pnas.94.18.9909
|View full text |Cite
|
Sign up to set email alerts
|

A signaling organelle containing the nerve growth factor-activated receptor tyrosine kinase, TrkA

Abstract: The topology of signal transduction is particularly important for neurons. Neurotrophic factors such as nerve growth factor (NGF) interact with receptors at distal axons and a signal is transduced by retrograde transport to the cell body to ensure survival of the neuron. We have discovered an organelle that may account for the retrograde transport of the neurotrophin signal. This organelle is derived from endocytosis of the receptor tyrosine kinase for NGF, TrkA. In vitro reactions containing semi-intact PC12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
139
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(142 citation statements)
references
References 75 publications
3
139
0
Order By: Relevance
“…The signaling endosome model proposes that upon ligand binding and activation, Trk receptors at the distal axon are internalized via clathrin-mediated [12][13][14] or pincher-dependent endocytosis [15,16]. The resultant vesicles containing the ligand-receptor complex are retrogradely transported to the cell body in order to mediate a survival response [3,[7][8][9][10][11]17, 18].…”
Section: Retrograde Axonal Transport Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signaling endosome model proposes that upon ligand binding and activation, Trk receptors at the distal axon are internalized via clathrin-mediated [12][13][14] or pincher-dependent endocytosis [15,16]. The resultant vesicles containing the ligand-receptor complex are retrogradely transported to the cell body in order to mediate a survival response [3,[7][8][9][10][11]17, 18].…”
Section: Retrograde Axonal Transport Mechanismsmentioning
confidence: 99%
“…Transport of activated receptors can occur even when minimal amounts of ligand are transported; indeed a single NGF dimer molecule is sufficient to maintain Trk activity during retrograde transport [19]. Vesicles containing neurotrophins and Trks have also been found to include activated components of the Ras-MAP kinase, PLCγ and PI3 kinase pathways [12,13,20,21]. These vesicles could therefore carry entire signaling complexes, capable of recapitulating in their entirety the signaling events that occurred at the nerve terminal [22].…”
mentioning
confidence: 99%
“…NGF binding to TrkA stimulates dimerization and autophosphorylation of tyrosine residues Tyr 499 , Tyr 679 , Tyr 683 , Tyr 684 , and Tyr 794 in the intracellular domain of the receptor, thereby creating sites for binding and activation of signaling intermediates (3) such as phospholipase C (PLC)-␥1 (4), adapter proteins Shc and FRS2 (5), and phosphatidylinositol 3Ј-kinase (6) that initiates the intracellular signaling cascades. It has been observed that NGF rapidly induces internalization of TrkA receptor to endocytic vesicles (7)(8)(9). The receptors within signaling vesicles remain catalytically active and phosphorylated because they are less accessible to membrane-associated phosphatases (10).…”
mentioning
confidence: 99%
“…The elucidation of the mechanism(s) used to transmit NGF signal from the terminals of axons to cell bodies of neurons is yet to be fully defined. In that retrograde NGF signaling is critical for the survival and maintenance of neurons of both the peripheral and central nervous systems, and the underlying mechanisms are likely to be shared by related neurotrophic factors, the issue remains one of the most significant and intriguing questions in neurobiology (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%